Two diode lasers versus ultrasonic activation of EDTA: push-out analysis and penetrability by confocal analysis - Pradelli, Jéssica Arielli [UNESP]; Kuga, Milton Carlos [UNESP]; Berbert, Fábio Luiz Camargo Vilella [UNESP] (Springer Nature, 2021)
EDTA solution removes smear layers; this function is more effective when the solution is agitated. The purpose of this study was to evaluate the protocol application of two diode lasers, compared with conventional energization or ultrasonic energization of 17% EDTA, evaluating the EDTA and AH Plus penetration capacity with laser confocal microscopy and push-out strength. In this study, human extracted teeth were used. The crowns were removed, and the root canal was prepared with a ProTaper system until the F5 file is reached, and irrigated with 2.5% sodium hypochlorite. The roots were randomly distributed in 5 groups (n=10): group control—flood with EDTA; conventional—flood with EDTA and agitation with K#45; ultrasonic—ultrasonic EDTA energization, TheraLase—EDTA energized with diode laser TheraLase surgery (808 nm, 2.8 W, pulsed mode, 20 Hz); and Gemini—EDTA energized with diode laser Gemini (810–980 nm, 2 W, pulsed mode, 50 Hz). The roots were obturated, using the single-cone technique and AH Plus. The EDTA solution was added with Malachite Green and AH Plus with Rhodamine B for evaluation with a laser confocal microscope. Specimens were sectioned in slices, one slice per third root, used in a laser confocal microscope and push-out strength. The data were submitted to normality test, analyzed using the Kruskal-Wallis test followed by Dun test, with a 5% level of significance (P < 0.05). The penetrability of EDTA and AH Plus was statistically different between the Ultrasonic, TheraLase, and Gemini groups when compared with other groups. However, when comparing ultrasonic with TheraLase and Gemini, there was no significant difference. In a push-out strength test, there was no significant difference, and the cohesive failures were predominant. In conclusion, the energization of 17% EDTA with any of the diode lasers improved only the penetrability of EDTA and AH Plus.
Keywords: Edetic acid; Lasers; Semiconductor; Ultrasonic therapy